'A State of Things Which Ought Not to be Permitted': Excavation of 19th-century slums (Bull Yard, Horn Yard, Swan Yard and Market Alley) surrounding Bank Street at 'The Charter', Gravesend - Ashley Tuck (Internet Archaeology)
Nineteenth-century remains in Gravesend (Kent, UK) were revealed by excavation, chiefly comprising buildings, along with wells and cesspits. Historic maps, newspaper archives and other sources have been used to interpret the majority of the site as a low status 'slum' accessed from narrow pedestrian passageways (Bull Yard, Horn Yard, Swan Yard and Market Alley). These areas comprised a poorly planned mixture of dwellings and premises including slaughterhouses, piggeries, warehouses and other commercial and small-scale industrial properties. A newspaper account described a view of the interiors of dwellings glimpsed through broken windows on Market Alley as 'A state of things which ought not to be permitted' (Gravesend and Dartford Reporter, 12 July 1879). Some parts of the site (Bank Street and Queen Street) were occupied by higher status dwellings and premises, including a medium-sized coach factory.